Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acs.jpca.7b02332
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Reactions of NO3 Radical with Methacrylate Esters

Abstract: Two different experimental methods (relative rate and absolute rate methods) were used to measure the rate coefficients for the reactions of NO radical with six methacrylate esters: methyl methacrylate (MMA, k), ethyl methacrylate (EMA, k), propyl methacrylate (PMA, k), isopropyl methacrylate (IPMA, k), butyl methacrylate (BMA, k), and isobutyl methacrylate (IBMA, k). In the relative rate method, the loss of the esters relative to that of a reference compound was followed in a 7300 L Teflon-walled chamber at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…The room-temperature rate coefficients obtained in this work and from the literatures (unit in cm 3 molecule -1 s -1 ) were used to conduct the calculations: kOH_MMA = 4.24×10 -11 , kOH_EMA = 4.99×10 -11 , kOH_nPMA = 4.86×10 -11 , kOH_nBMA = 5.26×10 -11 , kOH_iPMA = 5.36×10 -11 , kOH_iBMA = 5.27×10 -11 , kO3_MMA = 6.63×10 -18 , kO3_EMA = 7.74×10 -18 , kO3_nPMA = 8.46×10 -18 , kO3_nBMA = 9.78×10 -18 , kO3_iPMA = 10.94×10 -18 , kO3_iBMA = 9.96×10 -18 , kCl_MMA = 2.82×10 -10 (Blanco et al, 2009b), kCl_EMA = 2.71×10 -10 (Martin Porrero et al, 2010), kCl_nBMA = 3.72×10 -10 (Blanco et al, 2009b;Martin Porrero et al, 2010). kNO3_MMA = 2.98×10 -15 , k NO3_EMA = 4.67×10 -15 , kNO3_nPMA = 5.23×10 -15 , kNO3_nBMA = 7.91×10 -15 , kNO3_iPMA = 5.91×10 -15 , kNO3_iBMA = 6.24×10 -15 extracted from study of Zhou et al (2017).…”
Section: Conclusion and Atmospheric Implicationmentioning
confidence: 99%
See 2 more Smart Citations
“…The room-temperature rate coefficients obtained in this work and from the literatures (unit in cm 3 molecule -1 s -1 ) were used to conduct the calculations: kOH_MMA = 4.24×10 -11 , kOH_EMA = 4.99×10 -11 , kOH_nPMA = 4.86×10 -11 , kOH_nBMA = 5.26×10 -11 , kOH_iPMA = 5.36×10 -11 , kOH_iBMA = 5.27×10 -11 , kO3_MMA = 6.63×10 -18 , kO3_EMA = 7.74×10 -18 , kO3_nPMA = 8.46×10 -18 , kO3_nBMA = 9.78×10 -18 , kO3_iPMA = 10.94×10 -18 , kO3_iBMA = 9.96×10 -18 , kCl_MMA = 2.82×10 -10 (Blanco et al, 2009b), kCl_EMA = 2.71×10 -10 (Martin Porrero et al, 2010), kCl_nBMA = 3.72×10 -10 (Blanco et al, 2009b;Martin Porrero et al, 2010). kNO3_MMA = 2.98×10 -15 , k NO3_EMA = 4.67×10 -15 , kNO3_nPMA = 5.23×10 -15 , kNO3_nBMA = 7.91×10 -15 , kNO3_iPMA = 5.91×10 -15 , kNO3_iBMA = 6.24×10 -15 extracted from study of Zhou et al (2017).…”
Section: Conclusion and Atmospheric Implicationmentioning
confidence: 99%
“…It is important to point out that O3 could have also an important contribution to the loss of the unsaturated ester during the nighttime. Zhou et al (2017) have reported the tropospheric lifetimes of the studied species with respect to NO3 reactions (occurring mainly at nighttime) using the rate coefficients they have measured and [NO3] = 5 × 10 8 molecule cm -3 (Shu and Atkinson, 1995). The calculated lifetimes ranges from 70 to 186 hrs.…”
Section: Conclusion and Atmospheric Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental set up and the procedure used has been described in detail in a previous publication. 8 The rate coefficients for reactions (1-8) were measured by following the temporal profiles of NO3 and N2O5 in an excess of each alkane. The concentrations of NO3 and N2O5 were both measured via cavity ring down spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…[5] Azo dyes are widely used in textiles, leather articles, and food industries. [6] Recently, heteroaromatic scaffolds were considered to broaden their range of azo dye properties including azopyrimidine, [7] azopyridines, [8][9] azopyrroles, [10] azoimidazole, [11][12][13][14][15] azopyrazoles [16][17][18] and azoindazole scaffold. [19] They were used as photodissociable ligands in molecular switches and machines owing to their light driven cis/trans isomerisation.…”
Section: Introductionmentioning
confidence: 99%